The International Cooperation at STKIP Weetebula based on Hofstede’s Culture Dimensions - kii Yape Wilhelmus (Jurnal Edukasi Sumba (JES), 2020)
This paper describes the international cooperation between STKIP Weetebula (Indonesia), Misereor Germany, and The University of Osnabrück Germany based on Hofstede’s Cultural dimensions. The first part of this paper explains about the definition of culture, cross-cultural, and multicultural cooperation. The second part provides an overview about Hofstede’s Cultural Dimensions and the international cooperation at STKIP Weetebula particularly the cooperation between STKIP Weetebula and Misereor that includes The University of Osnabrück Germany. The third part of this paper explains international cooperation at STKIP Weetebula based on Hofstede’s Cultural Dimensions. Some of the explanations are from the result of the external evaluation of several international cooperation programs supported by Germany partners which include international partners such as Misereor, AGEH, The University of Osnabrück, and KMW.Cross Cultural, International Cooperation